Molecular Characterization and Genetic Variability of Trichoderma Harzianum Isolates by Using PCR-RAPD Markers - Al-Araji, Alaa Mohsen (Al-Nahrain Journal of Science, 2018)
The PCR-based technique of randomly amplified polymorphic DNA (RAPD) was used tocharacterize and assess the genetic relatedness of eight Trichoderma harzianum isolates. GenomicDNA of each species was extracted at a final concentration of 400 - 600 μg / 2-3 g of wet myceliumand at a purity of 1.6-1.8. Each DNA sample was amplified with each of 15 primers and theproducts were resolved electrophoretic ally on 1.2% agarose gel, stained with ethidium bromide andphotographed under UV. Six primers failed to support amplification while the remaining nineprimers produced a total of 128 main bands (11-20 per primer) across the eight isolates. Of thesebands, 120 (9-19 per primer) were polymorphic. The least efficient primer was OPY-19 (8.59),while the most efficient one was OP-B14 (15.63%). Primer OP-Y19 had the lowest (7.5%)discriminatory power while primer OP-B14 had the highest (15.8%). RAPD analysis fingerprintedsix of the eight isolates through unique bands with one or more of the 9 primers. Cluster analysisbased on the genetic distances split the eight isolates into two major group genotypes.